Superinfection with Difficult-to-Treat Pathogens Significantly Reduces the Outcome of Periprosthetic Joint Infections - Ali Darwich; Franz-Joseph Dally; Khaled Abu Olba; Elisabeth Mohs; Sascha Gravius; Svetlana Hetjens; Elio Assaf; Mohamad Bdeir (MDPI AG, 2021)
Periprosthetic joint infection (PJI) is a serious complication after total joint arthroplasty. In the course of a PJI, superinfections with pathogens that do not match the primary infecting micro-organism may occur. To our knowledge, there are no published data on the outcome of such infections in the literature. The aim of this study was to assess the outcome of PJI with superinfections with a difficult-to-treat (DTT) pathogen. Data of 169 consecutive patients with PJI were retrospectively analyzed in this single-center study. Cases were categorized into: Group 1 including non-DTT-PJI without superinfection, Group 2 DTT-PJI without superinfection, Group 3 non-DTT-PJI with DTT superinfection, and Group 4 non-DTT-PJI with non-DTT superinfection. Group 3 comprised 24 patients and showed, after a mean follow-up of 13.5 ± 10.8 months, the worst outcome with infection resolution in 17.4% of cases (p = 0.0001), PJI-related mortality of 8.7% (p = 0.0001), mean revision rate of 6 ± 3.6 (p < 0.0001), and duration of antibiotic treatment of 71.2 ± 45.2 days (p = 0.0023). PJI caused initially by a non-DTT pathogen with a superinfection with a DTT pathogen is significantly associated with the worst outcome in comparison to non-DTT-PJI, PJI caused initially by a DTT pathogen, and to non-DTT-PJI with a non-DTT superinfection.